2023
DOI: 10.1530/ec-23-0235
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric obesity and skin disease: cutaneous findings and associated quality-of-life impairments in 103 children and adolescents with obesity

Abstract: Objective: Little is known about specific cutaneous findings in children and adolescents with overweight and obesity. This study assessed the association of skin signs with pivotal auxological and endocrinological parameters and their influence on the quality of life of young people with obesity. Study design: All patients initially recruited for a tertiary hospital's weight control program were offered participation in this interdisciplinary, single-centre, cross-sectional study. All participants underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Thus, it may contribute to the increased incidence of cutaneous manifestations and disorders, such as acanthosis nigricans, hirsutism, striae distensae, acrochordons, keratosis pilaris, chronic venous insufficiency, plantar hyperkeratosis, cellulitis, psoriasis, skin infections, and hidradenitis suppurativa [ 213 ]. Numerous studies regarding the link between obesity and dermatological diseases among adults can be found in the literature; however, evidence for the pediatric population is scarce [ 214 ]. Nevertheless, a recent study of 103 children and adolescents with excessive body weight showed a high incidence of skin abnormalities occurring in this group [ 214 ].…”
Section: Non-metabolic Complications Of Obesity In Childrenmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, it may contribute to the increased incidence of cutaneous manifestations and disorders, such as acanthosis nigricans, hirsutism, striae distensae, acrochordons, keratosis pilaris, chronic venous insufficiency, plantar hyperkeratosis, cellulitis, psoriasis, skin infections, and hidradenitis suppurativa [ 213 ]. Numerous studies regarding the link between obesity and dermatological diseases among adults can be found in the literature; however, evidence for the pediatric population is scarce [ 214 ]. Nevertheless, a recent study of 103 children and adolescents with excessive body weight showed a high incidence of skin abnormalities occurring in this group [ 214 ].…”
Section: Non-metabolic Complications Of Obesity In Childrenmentioning
confidence: 99%
“…Numerous studies regarding the link between obesity and dermatological diseases among adults can be found in the literature; however, evidence for the pediatric population is scarce [ 214 ]. Nevertheless, a recent study of 103 children and adolescents with excessive body weight showed a high incidence of skin abnormalities occurring in this group [ 214 ]. Skin alterations were associated with increasing BMI and age, and the most prevalent were striae distensae (71%), keratosis pilaris (64.7%), acanthosis nigricans (45%), acne vulgaris (39.2%), acrochordons (25.5%), and plantar hyperkeratosis (17.6%) [ 214 ].…”
Section: Non-metabolic Complications Of Obesity In Childrenmentioning
confidence: 99%
See 3 more Smart Citations